Factors influencing consumers' intention to purchase products advertised on Facebook - Mert, Hasinat (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
The study investigated factors influencing consumers' intention to purchase products advertised on Facebook. Data was collected through structured questionnaires, and a total of 405 respondents were sampled. The respondents are existing Facebook users living in the Klang Valley, Malaysia. The study designed and proposed a conceptual model based on the existing Theory of Reasoned Action (TRA) model. It investigated the relationship between word of mouth, display advertising and attitudes toward products advertised on Facebook, and the relationship between subjective norms, attitudes and intention to purchase products on Facebook. To analyse the collected data, the study used SPSS and PLS-SEM. A factor analysis was used to extract significant constructs underlying the data followed by structural equation modelling to examine the fitness of the proposed model and test the hypotheses. Based on the outcomes, the study indicates that the TRA model is appropriate for this study because the relationships among the factors are positive. Three factors (display advertising, subjective norms and attitudes) are significant except for word of mouth. Display advertising revealed that there is a significant influence on attitude towards products advertised on Facebook, and attitudes and subjective norms have significant influence on purchase intention. The research findings can be beneficial for stakeholders in marketing and those using Facebook as a medium for advertising to attract consumers.